Conducting Polymers: The Role of Electrostatic Interaction between Free Charge Carriers and Counterions in Thermoelectric Power Factor of Conducting Polymers: From Crystalline to Polycrystalline Domains (Adv. Theory Simul. 6/2020). Issue 6 (5th June 2020) - Shi, Wen; Yildirim, Erol; Wu, Gang; Wong, Zicong Marvin; Deng, Tianqi; Wang, Jian‐Sheng; Xu, Jianwei; Yang, Shuo‐Wang
Abstract : In article number 2000015, new insights into thermoelectric transport in conducting polymers based on first‐principles calculations and new material design guidelines are presented by Shuo‐Wang Yang and co‐workers. They demonstrate that in the crystalline domains, the counterion scattering controls the power factor, and in the polycrystalline domains, the crystallite orientations and the grain sizes strongly affect the power factor.